A Revolution in Accounting Thought? - Wells, M. C. (The Accounting Review, 1976)
Abstract The notion of a revolution in accounting is taken from Thomas S. Kuhn's "The Structure of Scientific Revolutions. His thesis is that science does not progress through accumulation. Rather, a series of tradition shattering revolutions occur in which one time-honored scientific theory is rejected in favor of another incompatible with it. The new theory, or set of ideas, is unique in that it is not derived from the previously accepted dogma. It is seldom or never just an increment to what is already known and in the process of moving from the old set of ideas to the new, the community of scientists Follows a number of identifiable steps namely, recognition of anomalies, a period of insecurity, development of alternative sets of ideas, identification of schools of thought, domination of the new practices or ideas. The first step is a precursor to the whole process, it initiates the period of crisis which follows. During that period, scientists become increasingly dissatisfied with the existing theoretical framework and a search for alternatives begins. Therefore, the second and third steps are mutually interactive. As dissatisfaction grows, the search for alternatives gains impetus, as alternatives are discerned and discussed, the dissatisfaction is heightened. Schools of thought emerge and one set of ideas gradually gains ascendency over alternatives.